2006
DOI: 10.1111/j.1076-7460.2006.04830.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐Type Natriuretic Peptide Predicts Postdischarge Prognosis in Elderly Patients Admitted Due to Cardiogenic Pulmonary Edema

Abstract: To examine the prognostic role of predischarge B-type natriuretic peptide (BNP) levels in elderly patients admitted to the hospital due to cardiogenic pulmonary edema, 203 patients consecutively admitted to the Heart Failure Unit of the Cardiology Department were retrospectively evaluated. The primary clinical end point selected was a combination of: 1) deaths; plus 2) readmissions to the hospital for heart failure in the 6 months after discharge. Thirty-one deaths (15.3%) and 44 readmissions for heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Other studies have had varied follow-up time and heterogeneous endpoints. Among the studies to examine admission and discharge BNP values, several have also found that predischarge BNP was the most important prognostic marker (8,12,14,26). For example, the largest single-center study by Logeart and colleagues (n=114) revealed discharge BNP was the most important predictor of 6-month outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have had varied follow-up time and heterogeneous endpoints. Among the studies to examine admission and discharge BNP values, several have also found that predischarge BNP was the most important prognostic marker (8,12,14,26). For example, the largest single-center study by Logeart and colleagues (n=114) revealed discharge BNP was the most important predictor of 6-month outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Before implementation of B-type natriuretic peptide testing for discharge decision, we usually discharged patients when a clinical/instrumental finding of stability was achieved [16,17]. This finding was made if 6 criteria were simultaneously met: a) subjective improvement on the basis of NYHA class, or at least no orthopnoea, for refractory NYHA IV patients; b) 90 b systolic blood pressure b 120 mm Hg; c) heart rate b 100 bpm; d) pulse oxymetry in ambient air N 90%; e) diuresis N 1000 ml/day; f) improvement in fluid overload (normal hydration or slight hyper-or de-hydration on electrical impedance analysis) [18].…”
Section: Treatment and Clinical Criteria Of Stabilitymentioning
confidence: 99%
“…We used a Btype natriuretic peptide value of ≤250 pg/ml [19] or a reduction of ≥30% [20] with respect to admission to identify patients who could be discharged, provided that the favourable modifications in the neuro-hormone corresponded to the above mentioned clinical/instrumental finding of stability [16,17]. Patients with a B-type natriuretic peptide value of N 250 pg/ml, in the absence of a reduction of ≥30%, were given "aggressive" treatment, namely: a) increased diuretic treatment (up to 500 mg/day of furosemide), b) strict blood pressure and heart rate control: target valuesb 100 mm Hg (for systolic blood pressure) and b 80 bpm respectively), c) possible inclusion in the therapeutic regimen of i.v.…”
Section: B-type Natriuretic Peptide Use As a Further Criterionmentioning
confidence: 99%
“…In another study of 325 ED patients, BNP levels above 480 pg/mL could predict adverse outcomes with a sensitivity of 68% and a specificity of 88% and area under the ROC curve of 0.87 [62]. BNP assays have strong prognostic value in both elderly and diabetic patients [63,64] and may be a stronger predictor in women compared to men [65].…”
Section: Relative Value Of Bnp and Nt-probnp In Heart Failure Prognosismentioning
confidence: 99%